1989
DOI: 10.1007/bf00152766
|View full text |Cite
|
Sign up to set email alerts
|

Dark adaptation compared with electrooculography in primary biliary cirrhosis

Abstract: In a series of asymptomatic patients with primary biliary cirrhosis there was a significant impairment of dark adaptation thresholds as compared with a control group. Vitamin A levels were abnormally low in only two of the patients and these two both showed high dark adaptation thresholds. The electrooculogram was reduced in only the most severely affected case. It is suggested that visual function tests should be performed alongside vitamin A level measurements before deciding on treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Impaired night vision has been recognized in alcoholic cirrhotics since the late 1930s, and this has been confirmed in recent studies in many types of cirrhosis 39 41 . This is usually associated with vitamin A deficiency, and vitamin A supplementation improved night vision.…”
Section: Clinical Manifestations Of Zinc Deficiencymentioning
confidence: 79%
“…Impaired night vision has been recognized in alcoholic cirrhotics since the late 1930s, and this has been confirmed in recent studies in many types of cirrhosis 39 41 . This is usually associated with vitamin A deficiency, and vitamin A supplementation improved night vision.…”
Section: Clinical Manifestations Of Zinc Deficiencymentioning
confidence: 79%
“…Underperception of night blindness has been reported by others in ALD,13 PBC14 24 and also in malnutrition. Our study confirmed underperception of impairment of DA which is a risk to patient safety.…”
Section: Discussionmentioning
confidence: 67%
“…Underperception of impaired DA has been reported in ALD and primary biliary cirrhosis (PBC) 13 14. Lack of perception of impairment is a risk to patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Ten female PBC patients, with a mean (± SEM) age of 62.8 ± 3.2 (range 45-74) years and diagnosed 7.8 ± 1.7 (0. [8][9][10][11][12][13][14] years previously, were asked to participate in the study. The mean duration of symptomatic disease was 9.4 ± 1.8 (2.3-14.8) years.…”
Section: Patientsmentioning
confidence: 99%